O Programa Oeste em Desenvolvimento e seus impactos na governança da região Oeste do Paraná - Chibiaqui, Eloiza Dal Pozzo (2020)
In this work, the focus of study was the Programa Oeste em Desenvolvimento (POD), a governance structure whose objective is to promote the development of the West of Paraná through the synergy between public and private organizations. The POD was analyzed based on documentary research and semi-structured interviews with 45 professionals who played a major role in the Program. It was found that the regional economic development occurs satisfactorily, but the institutional environment showed some weaknesses, such as the lack of trust between the participants, vertical relations and lack of mobilization towards joint action between the actors, with the need to invest in interactions and in the collaborative process between them. In order to manage conflicts, the POD needs to review its management processes so that it happens in a horizontal and democratic way. Throughout the thesis, discussions and suggestions are presented for the POD to be strengthened as a democratic, transparent space that balances power relations and, thus, can consolidate and legitimize its representativeness and generate the desired regional development.